(untitled) (ASEAN Legal Insights, 2024)
Trafficking in persons (TIP), is a severe violation of human dignity and rights. The Palermo Protocol brought the issue of TIP to the world’s attention and established a standard approach for state parties to address TIP, known as the “3Ps” model, which seeks to prosecute perpetrators, protect victims and prevent TIP. Despite Thailand passing the Anti Trafficking in Persons Act B.E.2551 (ATIPA 2008), the number of TIP cases is still rising. This article aims to discuss the Palermo Protocol, the ATIPA 2008, to examine whether the ATIPA 2008 complies with the Palermo Protocol and evaluate the implementation of the ATIPA 2008 by examining Thailand’s approach in the TIP Report 2024. The methodology used is a doctrinal legal method where both primary and secondary data sources are used and content analysis and analytically analysed. The paper presented the prevalence of TIP in Thailand and the Palermo Protocol and the ATIPA 2008 and evaluate the implementation of the ATIPA 2008. This study found that ATIPA 2008 complies with the Palermo Protocol. Among analysis are the problem of identifying labour trafficking, accommodations and interpreters, corruption, undergoing the MDT identification process, training on SOPs for identifying labour trafficking, understanding of trafficking, implementation of victim identification procedures, shelter stays with movement and communication restrictions, benefits and protection of workers, measuring work and rest hours, and identify forced labour cases. The authors found that despite legislative progress, weak enforcement significantly contributed to its ineffectiveness. Therefore, enforcement needs to be strengthened to address and eliminate the problem of TIP in Thailand.